2011
DOI: 10.4111/kju.2011.52.3.189
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Surgical Strategy for Patients with Benign Prostatic Hyperplasia: 12-Year Single-Center Experience

Abstract: PurposeThe purpose of this study was to evaluate the annual changes in prostate variables and style of surgical treatment of patients with benign prostatic hyperplasia (BPH) over the past 12 years.Materials and MethodsThe subjects were 918 patients (January 1999-November 2010) who were treated by either open prostatectomy or transurethral resection of prostate (TURP). Every year, the performance ratio between open prostatectomy and TURP was evaluated. Before surgery, total and transitional zone volumes of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…[1], reported mean resected tissue weight of 28.4 g in a large community cohort, suggesting that resection of larger prostates in the contemporary era was most likely. Shin and Park [9] have also reported an increase in the PV of their contemporary TURP series. Despite this, resected prostate weight increased and resection time decreased suggesting improved resection efficiency (resection volume per minute of TURP).…”
Section: Discussionmentioning
confidence: 89%
“…[1], reported mean resected tissue weight of 28.4 g in a large community cohort, suggesting that resection of larger prostates in the contemporary era was most likely. Shin and Park [9] have also reported an increase in the PV of their contemporary TURP series. Despite this, resected prostate weight increased and resection time decreased suggesting improved resection efficiency (resection volume per minute of TURP).…”
Section: Discussionmentioning
confidence: 89%
“…This study showed that the mean prostate volume was significantly greater in group 3 than in group 1; simultaneously, the weight of the resected tissue was also significantly greater in subgroup 3 than in subgroup 1. Shin and Park [ 14 ] reported that the mean resection volume increased with both TURP and open prostatectomy between 1999 and 2010. Reich et al [ 15 ] evaluated 10,654 patients who underwent TURP and showed that mortality and morbidity were closely associated with the weight of tissue resected.…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated by TURP show an increase in not only prostate volume but also resected prostate volume, which may be because the surgery was delayed by treatment with α-1 blockers or 5-α reductase inhibitors [ 16 ].…”
Section: Discussionmentioning
confidence: 99%